2012
DOI: 10.4161/cc.22937
|View full text |Cite
|
Sign up to set email alerts
|

Hyper-mitogenic drive coexists with mitotic incompetence in senescent cells

Abstract: When the cell cycle is arrested, even though growth-promoting pathways such as mTOR are still active, then cells senesce. For example, induction of either p21 or p16 arrests the cell cycle without inhibiting mTOR, which, in turn, converts p21/p16-induced arrest into senescence (geroconversion). Here we show that geroconversion is accompanied by dramatic accumulation of cyclin D1 followed by cyclin E and replicative stress. When p21 was switched off, senescent cells (despite their loss of proliferative potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(99 citation statements)
references
References 59 publications
3
94
1
Order By: Relevance
“…However, the cyclin E-CDK2 kinase targets Rb and other pocket proteins, which have important roles as tumor suppressors during G 2 /M as well as at the G 1 /S phase chromatin decondensation [43][44][45][46] or histone biosynthesis, 47,48 both of which are associated with genomic instability. 49,50 Finally, it is possible that like cyclin E1, cyclin E2 stimulation of S phase entry may promote replication stress and consequent genomic instabilty when uncoupled from other growth-promoting cellular processes, 24,51 although whether the two E-type cyclins play similar roles in DNA replication remains to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the cyclin E-CDK2 kinase targets Rb and other pocket proteins, which have important roles as tumor suppressors during G 2 /M as well as at the G 1 /S phase chromatin decondensation [43][44][45][46] or histone biosynthesis, 47,48 both of which are associated with genomic instability. 49,50 Finally, it is possible that like cyclin E1, cyclin E2 stimulation of S phase entry may promote replication stress and consequent genomic instabilty when uncoupled from other growth-promoting cellular processes, 24,51 although whether the two E-type cyclins play similar roles in DNA replication remains to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…21 In addition, cyclin E2 overexpression, but not cyclin E1 overexpression, is associated with shorter survival in some breast cancer subgroups and vice versa. 20,22 Several studies have shown that overexpression of cyclin E1 affects mitotic progression and promotes genomic instability, 7,9,10,23,24 but cyclin E2 has not been studied in this context. Given the strong role for mitotic disregulation and genome instability in human cancer, we characterized the effects of cyclin E2 on these endpoints in estrogen receptor-positive breast cancer cells, a subtype that overexpresses cyclin E2 more strongly than cyclin E1.…”
Section: Introductionmentioning
confidence: 99%
“…79 Accumulation of cyclin D1 and E1 was also observed in G2-arrested cells following ectopic induction of p21. 80 More recently, it has been shown that in telomerase-negative cells eroded telomeres elicit DDR predominantly in G2, leading to p53/p21-dependent cell cycle arrest/ exit with 4N DNA content. 81 Unlike functional telomeres that trigger a transient DNA damage response in G2 that is required for their protection, 82 telomeric DNA damage in aging cells persists at a subset of the shortest telomeres and fully activates DDR.…”
Section: Senescence In G2 -An Old Concept Awaiting Wider Recognitionmentioning
confidence: 99%
“…46 Rapamycin targets mTOR pathways, inhibits DNA damage response (or pseudo-DNA damage response), and therefore slows down cellular senescence. [47][48][49] In this scenario, it would be interesting to examine whether rapamycin could rescue the defective chromatin remodeling and defective DNA repair in Zmpste24-null cells in future study. Nevertheless, our data shed new light into molecular basis of HP1α in heterochromatin misorganization, delayed DNA damage response, and early senescence in Zmpste24-deficient progeria mouse model, providing an additional intervention target for progeria and normal aging.…”
Section: Discussionmentioning
confidence: 99%